2022
DOI: 10.3390/antibiotics11111661
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physcion and Chitosan Can Efficiently Control Powdery Mildew in Rosa roxburghii

Abstract: Powdery mildew is an extremely serious disease of all Rosa roxburghii production regions in China and frequently causes 30~40% of economic losses. Natural products are considered excellent alternatives to chemical fungicides. In this work, we investigated the efficacy of physcion used together with chitosan controls R. roxburghii powdery mildew and impacts its resistance, growth, yield, and quality. The results reveal that the foliar application of 12.5 mg L−1 0.5% physcion aqueous solutions (AS) + 250 mg L−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Many studies have proven that physcion can control powdery mildew caused by B. graminis, P. xanthii, S. fuliginea, etc. [25][26][27][28]. According to Zhao and Xia [28], 0.05% physcion SC can effectively control powdery mildew in strawberry, tomato, cucumber, and grapes with a control effect of 70~80%.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proven that physcion can control powdery mildew caused by B. graminis, P. xanthii, S. fuliginea, etc. [25][26][27][28]. According to Zhao and Xia [28], 0.05% physcion SC can effectively control powdery mildew in strawberry, tomato, cucumber, and grapes with a control effect of 70~80%.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have proved that physcion could control powdery mildew caused by B. graminis, P. xanthii, S. fuliginea, etc. (Choi et al ., 2004;Yang et al, 2013;Zhang et al, 2022;Zhao and Xia, 2021). According to Zhao and Xia (2021), 0.05% physcion SC could effectively control powdery mildew in many crops under suitable concentration with control effect of 70%~80%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the reduced use of chemical pesticides and supplemental or alternative methods for plant disease management have attracted increasing attention [ 40 , 41 , 56 ]. Some reports have indicated that chitosan could be applied as an efficient adjuvant to enhance isopyrazam·azoxystrobin, tetramycin, pyraclostrobin, allicin, and physcion to control leaf spot and powdery mildew in various plants [ 28 , 40 , 41 , 42 , 43 ]. The present study found that compared with treatment using high-dosage difenoconazole or chitosan alone, chitosan used with low-dosage difenoconazole more effectively controlled leaf spot disease in P. heterophylla and enhanced its disease resistance, photosynthesis, quality, and yield, as well as effectively reducing difenoconazole application.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report also indicated that chitosan spraying effectively enhanced the growth, photosynthesis, resistance, yield, and quality of the continuous cropping of Pinellia ternata [ 39 ]. Meanwhile, chitosan can be applied as an effective adjuvant to promote isopyrazam·azoxystrobin and tetramycin, or pyraclostrobin, allicin, and physcion to control kiwifruit leaf spot or Rosa roxburghii powdery mildew, and reduce their application dosage [ 28 , 40 , 41 , 42 , 43 ]. Overall, whether chitosan can ameliorate the control effect of difenoconazole on leaf spot disease in P. heterophylla and whether their co-application can more effectively enhance the growth, quality, and yield of P. heterophylla is also worth further study.…”
Section: Introductionmentioning
confidence: 99%